A Compendium of Partnerships between Government and Voluntary Sector All India Conference on the Role of the Voluntary Sector in National Development 20th April, 2002 - Planning Commission (Planning Commission, 2002)
Voluntarism is a phenomenon of long cherished tradition established in ancient India and proclaimed by people to share skills, ideas, philosophy, expertise, services, resources, assets and knowledge among the members of different communities living together across the country. Voluntarism is the central core of social action in a democratic society. Voluntarism manifests through organizations, associations, individuals and organized civil structures such as Voluntary Organizations (VOs), Non Governmental Organizations (NGOs), cooperatives of different types and micro-credit organizations outside the governmental bureaucratic machinery.
Planning Commission Government of India
Planning Commission Government of India